2021
DOI: 10.3390/children8030219
|View full text |Cite
|
Sign up to set email alerts
|

“You Can’t Go to the Park, You Can’t Go Here, You Can’t Go There”: Exploring Parental Experiences of COVID-19 and Its Impact on Their Children’s Movement Behaviours

Abstract: The COVID-19 outbreak and related public health guidelines have changed the daily lives of Canadians and restricted opportunities for healthy movement behaviours for children. The purpose of this study was to explore how parents experienced the pandemic-related restrictions and how they impacted their children’s movement behaviours. Methods: Twenty-nine semi-structured one-on-one interviews were conducted (June–July 2020) with parents of children (5–11 years old) in Ontario and British Columbia. Interviews las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 26 publications
5
102
0
2
Order By: Relevance
“…Results of this study showed that public health preventive measures practiced by children were associated with a decrease in outdoor time and an increase in screen time during the COVID-19 pandemic between April 14 and July 15, 2020. The findings from this study contribute to the growing evidence demonstrating that the COVID-19 pandemic is associated with unhealthy movement behaviours among Canadian children (Moore et al 2020 ; McCormack et al 2020 ; Riazi et al 2021 ).…”
Section: Discussionsupporting
confidence: 66%
“…Results of this study showed that public health preventive measures practiced by children were associated with a decrease in outdoor time and an increase in screen time during the COVID-19 pandemic between April 14 and July 15, 2020. The findings from this study contribute to the growing evidence demonstrating that the COVID-19 pandemic is associated with unhealthy movement behaviours among Canadian children (Moore et al 2020 ; McCormack et al 2020 ; Riazi et al 2021 ).…”
Section: Discussionsupporting
confidence: 66%
“…In a recent study, Canadian parents of children ages 5 to 11 years noted the decline in their child's physical activity levels was due to, in part, their reliance on pre-programmed, structured activities to keep their child active. Parents felt tasked with the challenge of reimagining ways to increase physical activity and decrease sedentary behaviours during the pandemic (Riazi et al, 2021). Further, parents had expressed the challenge of controlling their child's screen time, stating this as a way for their child to connect with friends and complete schoolwork (Riazi et al, 2021).…”
Section: Summary Of Ndingsmentioning
confidence: 99%
“…Factors associated with an increase in physical activity during the pandemic were family encouragement, parental engagement, and dog ownership [ 16 ]. Variation in changes to movement behaviours during the pandemic has been attributed to regional difference in public health policies including school, facility and park closures [ 21 , 22 ], neighbourhood environments such as population density and proximity to major roads [ 20 ], and family-level factors such as living in a single-family versus multi-family dwelling [ 16 , 23 ]. Previous qualitative work conducted in urban areas has identified parental stress, uncertainty in navigating pandemic restrictions, and reduced access to green spaces as factors negatively impacting children’s movement behaviours during COVID-19 [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Variation in changes to movement behaviours during the pandemic has been attributed to regional difference in public health policies including school, facility and park closures [ 21 , 22 ], neighbourhood environments such as population density and proximity to major roads [ 20 ], and family-level factors such as living in a single-family versus multi-family dwelling [ 16 , 23 ]. Previous qualitative work conducted in urban areas has identified parental stress, uncertainty in navigating pandemic restrictions, and reduced access to green spaces as factors negatively impacting children’s movement behaviours during COVID-19 [ 23 ]. Given the noted impact of community and neighbourhood environments on children’s movement behaviours during the pandemic [ 16 , 20 ], it is important to explore the experiences of families living in a variety of contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation